CAREER COUNSELLOR GUIDANCE FOR SECONDARY SCHOOL STUDENTS IN CAREER DECISION-MAKING PROCESS - Drozdovs, Vitalijs (Education Reform: Education Content Research and Implementation Problems, 2019)
In globalization era career management has been changed. The individual is now responsible for the decisions he or she will make in terms of career. The problem is crucial for secondary school students, as when they graduate secondary school they should know what they going to do next. Some students leave a career decision to the latest moment; however it may lead to serious problems as career uncertainty may impact students’ future career. Career counsellor may guide students, although the final decision about future profession choice should be made by them. The paper provides theoretical framework of career guidance system in Latvia. 76 secondary school students were involved in the study from Rezekne Polish State Gymnasium. The results of the study showed that secondary school students think about their future profession. However, most of the secondary students do not plan to attend career counsellor. Various factors may affect students’ decisions about their future career, though most of them rely on their own opinion.